Pengaruh Financial Distress dan Profitabilitas terhadap Penghindaran Pajak pada Perusahaan Sub Sektor Farmasi yang Terdaftar di BEI tahun 2020-2022 - Feni Monika Silalahi; Richard Friendly Simbolon (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Taxes play an important role, but the realization of tax revenues is not yet optimal, this is due to the low level of taxpayer compliance in Indonesia and there are still actors who commit tax evasion. This research aims to present a review of the effects of profitability and financial distress on tax avoidance. The empirical research carried out focuses on companies belonging to the pharmaceutical category listed on the Indonesia Stock Exchange (BEI) during the 2020-2022 period. This research uses secondary data available in the annual report which can be accessed via the official IDX website. The author in his research also used a purposive sampling method with conditions set by the author. The subjects of this research were 12 companies over a period of 3 years of research so that the author obtained 36 observation data. In his research, the author used multiple linear regression methods as well as descriptive statistical analysis techniques, classical hypothesis testing and hypothesis testing including goodness of fit (F-test) as well as the coefficient of determination (R2). The research data was processed using SPSS 22 software and the output showed that profitability and financial distress had no impact on tax avoidance behavior.